The Capability to a chive An Effective Marketing Performance In Banks: applied Study in a sample of Iraqi Banks (Journal of Accounting and Financial Studies ( JAFS ), 2012)
The marketing of banking service is considered to be one of the impotent fields which showed a universal inebriates . He research showed the comparison between the application of marketing in ideas and application for loot government and private Iraqi bank. The research comets of four parts; Mythology / the concept and the importance of Banking Marketing / Research applichlion/ Conelnion and  recommendation.